2022
DOI: 10.1007/s15010-022-01911-x
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric hospital admissions, case severity, and length of hospital stay during the first 18 months of the COVID-19 pandemic in a tertiary children’s hospital in Switzerland

Abstract: Background SARS-CoV-2 directly contributes to the burden of respiratory disease in children, but indirect effects of protective measures also need to be considered to assess the overall impact of the pandemic on children's health. Methods We retrospectively compared pre-pandemic and pandemic data of main admission diagnoses, sorted by ICD-10 diagnosis groups, in a tertiary children's hospital in Switzerland from 2017 until August 2021. Hospital admission r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
5
0
2
Order By: Relevance
“…Increased concern about the new condition, might prompt more hospital admissions in the early phase of the COVID-19 pandemic. Literature, however, suggests that an increased fear of possible infection with SARS-CoV-2, resulted in a reduction of medical consultation and hospital admission for respiratory infections [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Increased concern about the new condition, might prompt more hospital admissions in the early phase of the COVID-19 pandemic. Literature, however, suggests that an increased fear of possible infection with SARS-CoV-2, resulted in a reduction of medical consultation and hospital admission for respiratory infections [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature has also discussed the impact of the COVID-19 pandemic. Still, the literature does not have estimates of the magnitude of the COVID-19 pandemic “effect size” on clinical and financial outcomes in a structural model [ 9 , 30 , 41 , 45 , 56 , 60 , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] ]. Previous publications have also not provided information on the relationship between the COVID-19 pandemic, patient condition, cost risk, and clinical and financial outcomes, as well as the effect of the season as a confounder in two structural models, the child model and the adult model.…”
Section: Discussionmentioning
confidence: 99%
“…In the UK, the RSV season is defined as the period from October to March with a peak incidence in December [ 5 , 31 , 32 ]. In two studies from Switzerland and Croatia, the increased incidence occurred between November and March, with the peak incidence in January [ 33 , 34 ]. The results presented in our study confirm trends observed in other European countries.…”
Section: Discussionmentioning
confidence: 99%